The Comparison of Halal Product Supervision Systems in Indonesia and Malaysia: Analysis of Legal Framework, Procedures, and Implementation Effectiveness - Nur Fauziyah; Shidqie, Azzam; Achmad Room Fitrianto (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2026)
This study aims to compare the halal product monitoring systems in Indonesia and Malaysia, focusing on the legal framework, responsible institutions, and certification and supervision procedures. As two countries with a majority Muslim population, Indonesia and Malaysia have an important role in ensuring the halal status of products circulating in the domestic and international markets. In Indonesia, halal supervision is regulated in Law No. 33 of 2014 concerning Halal Product Assurance, which establishes the Halal Product Assurance Agency (BPJPH) as the main authority. Meanwhile, Malaysia relies on the Malaysian Department of Islamic Development (JAKIM), which has been internationally recognized as a halal certification authority. The study found that although the two countries have similar standards and regulations, there are significant differences in the implementation of supervision, technology integration, and international recognition. Malaysia excels in implementing an integrated and efficient system, while Indonesia still faces challenges in implementing comprehensive regulations. The findings of this study are expected to be recommendations to improve the effectiveness of halal product monitoring, especially in Indonesia, by taking lessons from the system implemented in Malaysia.